Enriching the English Students’ Speaking Ability using Recount Story Telling with Guided Questions at STKIP Muhammadiyah. - Ahmad Arkan Ramadhani (LP3M Universitas Muhammadiyah Makassar)
ABSTRACTApplying appropriate technique to expand the students speaking ability is the English lecturer’s responsibility in STKIP Muhammadiyah Bulukumba to create the situation. Recount Storytelling with Guided Question is a technique in generating speaking class more fun, enjoyable, and memorable for the students. This research aims at: (1) finding out whether or not recount storytelling technique with guided questions improve the students speaking ability and (2) knowing the students' attitude toward the use of recount storytelling technique with guided questions in learning speaking.This research will employ quasi experimental design. The population of this research is the students of English department at STKIP Muhammadiyah Bulukumba in academic year 2016/2017. The sample of this research consists of two groups of students; control and experimental group. The research data will be collected by using speaking test through interview and questionnaire which are analyzed by descriptive and inferential statistic through SPSS program.By discipline, this research is under the field of applied linguistics in finding out the effectiveness of using recount storytelling technique with guided questions to improve the students’ speaking ability and the attitude of the students. By activity, the students in the experimental group are introduced and taught by applying Recount Storytelling with Guided Question. At last, the students’ speaking ability in both groups will be compared to see whether there is a different achievement after they are treated by different technique in learning English speaking skill.Keywords: Recount Storytelling, Guided Questions, Attitude and Speaking skill